Use of priming agents for kale seedling production - da Silva, A. L.B.R.; da Silva, T. R.; Jones, Z.; Foshee, W.; Candian, J. S. [UNESP]; Cardoso, A. I.I. [UNESP] (International Society for Horticultural Science (ISHS), 2023)
The Objective s of this study were to characterize the seed imbibition process of kale seeds, evaluate the effect of three priming techniques on kale seedling production, and identify a priming strategy that increases the emergence, vigor, and growth of kale seedlings. Using three priming agents: water (seeds imbibed for 3, 6, 9, and 12 h), polyethylene glycol 6000 (PEG6000) (seeds imbibed at -0.2, -0.4, -0.6, and -0.8 MPa with kale seeds imbibed for 4, 8, 12, and 16 h), and Progibb® LV; (seeds imbibed at 0.5, 1.0, 1.5, and 2.0 g a.i. L-1for 15, 30, 45, and 60 min), and three kale cultivars ('Red Russian', 'Blue Ridge', and 'Siberian'), three experiments evaluated kale seedling parameters, including emergence speed index (ESI) and total emergence (TE) in a complete randomized block design (n=4) each. Water imbibition for 3 h provided the highest ESI and TE in the hydropriming experiment. In the hormonal priming experiment, Progibb® LV at 0.5% a.i. imbibed for 15 min provided the highest ESI and TE. In the osmopriming experiment, PEG6000 at 0.2 MPa for 16 h provided the highest ESI and TE. Once the best treatment of each experiment was compared to a control treatment, in which no priming agents were used, only the water imbibition for 3 h presented higher ESI than the control. However, this increment was only 1% higher, indicating that priming agents on kale seedling production should be focused on seedling quality rather than emergence rate.
Keywords: emergence speed index; hormonal priming; hydropriming; osmopriming; total emergence